Bi2OS2: a direct-gap two-dimensional semiconductor with high carrier mobility and surface electron states. Issue 6 (3rd October 2018) - Zhang, Xiwen; Wang, Bing; Niu, Xianghong; Li, Yunhai; Chen, Yunfei; Wang, Jinlan
Abstract : Bi2 OS2 nanosheets possess tunable anomalous layer-dependent bandgaps, derived from the synergetic effect of the quantum confinement and surface electron states. Abstract : Two-dimensional (2D) semiconductors with desirable band gaps and high carrier mobility are highly sought after for future application in nanoelectronics. Herein, by means of first-principles calculations, we predict that a new 2D material, namely a Bi2 OS2 nanosheet, possesses not only a tunable direct band gap, but also ultra-high electron mobility (up to 26 570 cm 2 V −1 s −1 ). More interestingly, an anomalous layer-dependent band gap is revealed, derived from the synergetic effect of the quantum confinement and intrinsic surface electron states. 2D Bi2 OS2 also exhibits excellent absorption over the entire solar spectrum and the absorption coefficient is comparable to that of inorganic–organic hybrid perovskite solar cells. Moreover, the Bi2 OS2 monolayer maintains good structural integrity up to 1000 K and has a relatively small exfoliation energy from its layered bulk. The excellent electronic and optical properties, together with high stability and great experimental possibility, render 2D Bi2 OS2 a promising material for future nanoelectronic and optoelectronic applications.